Hysterectomy Among Jordanian Females with Intellectual Disability and Autism - Mahmoud Gharaibeh; Abed Alrazaq H. Alhassan; Ghada Alhassan; Ibtisam Aref Karkaz; Leen Mohammad Al-Hourani (The International Journal of Health, Wellness, and Society, 2026)
Hysterectomy remains a frequently performed surgical procedure for females with disabilities, despite significant ethical, legal, and health concerns. The present study investigates the socio-demographic and attitudinal factors that influence Jordanian parents’ decisions regarding hysterectomy for their daughters with intellectual disability (ID) and autism spectrum disorder (ASD). A cross-sectional survey design was employed. A total of two hundred parents (100 male, 100 female) of daughters with ID (n = 109) or ASD (n = 91) participated. A researcher-developed forty-four-item questionnaire assessed four dimensions: (1) fear of sexual assault, (2) menstrual management difficulties, (3) knowledge and misinformation about hysterectomy, and (4) perceived lack of institutional and financial support. Cronbach’s alpha for the overall scale was 0.936, indicating excellent internal consistency. Frequencies and chi-square analyses were conducted using SPSS, version 27. Significant gender-based differences were observed across all four dimensions (p < 0.0001 for each), with fathers expressing greater concern about sexual assault and hysterectomy knowledge, while mothers reported greater difficulties with menstrual management. No statistically significant differences were observed between parents of children with ASD versus ID across any dimension. Income level was significantly associated with parental perceptions across all dimensions (p < 0.0001), with lower-income parents reporting higher concern about menstrual management and lack of support. In conclusion, family burden, culture-based stigma, and structural inadequacies are often the primary drivers behind hysterectomy in this context, and not the best interests of the person with the disability. The findings emphasize the need for a legal reform, family education, and integrated disability support services in Jordan.